The modelling of bifurcations of the statistical distributions of the concentrations of ammonia nitrogen in the river Desna - Osadchiy, V. I.; Osadcha, N. N.; Kovalchuk, L. A.; Skrynyk, O. Y. (Reports of the National Academy of Sciences of Ukraine, 2016)
Stochastic bifurcations of the probability density of the nitrogen concentration of ammonia in the river Desna are explained as a result of the accidental coincidence of two natural processes: reduced water flow and high thermal background. The reliability of the output is about 75 %. The modeling is done with a stochastic differential equation with the control parameter.